Influence of different elicitors on BIA production in Macleaya cordata - Peng Huang (Nature Portfolio, 2021)
Abstract Sanguinarine (SAN) and chelerythrine (CHE) have been widely used as substitutes for antibiotics for decades. For a long time, SAN and CHE have been extracted from mainly Macleaya cordata, a plant species that is a traditional herb in China and belongs to the Papaveraceae family. However, with the sharp increase in demand for SAN and CHE, it is necessary to develop a new method to enhance the supply of raw materials. Here, we used methyl jasmonate (MJ), salicylic acid (SA) and wounding alone and in combination to stimulate aseptic seedlings of M. cordata at 0 h, 24 h, 72 h and 120 h and then compared the differences in metabolic profiles and gene expression. Ultimately, we found that the effect of using MJ alone was the best treatment, with the contents of SAN and CHE increasing by 10- and 14-fold, respectively. However, the increased SAN and CHE contents in response to combined wounding and MJ were less than those for induced by the treatment with MJ alone. Additionally, after MJ treatment, SAN and CHE biosynthetic pathway genes, such as those encoding the protopine 6-hydroxylase and dihydrobenzophenanthridine oxidase enzymes, were highly expressed, which is consistent with the accumulation of SAN and CHE. At the same time, we have also studied the changes in the content of synthetic intermediates of SAN and CHE after elicitor induction. This study is the first systematic research report about using elicitors to increase the SAN and CHE in Macleaya cordata.